<htm> Tityus (Atreus) timendus Pocock, 1898 (Scorpiones, Buthidae), an enigmatic scorpion from Ecuador </htm> - Lourenço, W. R. (Acta Biológica Paranaense, 2012)
<htm> Tityus (Atreus) timendus Pocock, 1898 (Scorpiones, Buthidae), an enigmatic scorpion from Ecuador </htm>